Comment: How mutant HFE causes hereditary hemochromatosis - Muckenthaler, Martina (Blood, 2014)
In this issue of Blood, Wu et al describe the molecular function of HFE, the gene most commonly mutated in hereditary hemochromatosis (HH).1 HH is the most freq